Pseudoprogression in patients treated with immune checkpoint inhibitors for microsatellite instability-high/mismatch repair-deficient metastatic colorectal cancer. (February 2021) - Colle, Raphael; Radzik, Anna; Cohen, Romain; Pellat, Anna; Lopez-Tabada, Daniel; Cachanado, Marine; Duval, Alex; Svrcek, Magali; Menu, Yves; André, Thierry
Abstract: Background: The efficacy of immune checkpoint inhibitors (ICIs) in microsatellite instability-high/DNA mismatch repair (MSI/dMMR) metastatic colorectal cancer (mCRC) is well established. ICIs are responsible for pseudoprogression (PSPD) that complicates clinical decisions. We evaluated the PSPD frequency in patients with MSI/dMMR mCRC treated with ICIs. Patients and methods: Consecutive patients with MSI/dMMR mCRC treated with ICIs from February 2015 to December 2019 at Saint-Antoine Hospital were included. Imaging was retrospectively and centrally reviewed according to Response Evaluation Criteria in Solid Tumours, version 1.1 (RECIST 1.1) and immune RECIST (iRECIST). PSPD was defined as an unconfirmed disease progression by iRECIST. Results: One hundred twenty-three patients with MSI/dMMR mCRC were included. Thirty-six patients (29%) had radiological PD according to RECIST 1.1 during the median follow-up of 22.3 months (95% confidence interval [CI], 1.5–62.2), including 22 in the first 3 months (the primary radiological PD). Twenty-nine patients continued ICIs beyond PD. Twelve patients experienced PSPD, representing 10% of the population and 52% of the primary radiological PD. The median time to PSPD was 5.7 weeks (95% CI, 4.1–11.4). No PSPD was observed after 3 months. The PSPD incidence was 14.8% in patients treated with anti-PD1 alone (n = 9/61) and 4.8% in case of anti-PD1 plus anti-CTLA-4 (n = 3/62). Eight patients with PSPD experienced an objective response. The 2-year progression-free survival and overall survival rates for patients with PSPD were 70.0% (95% CI, 32.9–89.2) and 75.0% (95% CI, 29.8–93.4), respectively. Conclusion: Patients with MSI/dMMR mCRC treated with ICIs experienced PSPDs. PSPD occurred within the first 3 months and represented most of the primary radiological PDs. The use of iRECIST criteria should be questioned after 3 months. Highlights: Ten percent of patients with microsatellite instability metastatic colorectal cancer experience pseudoprogression. Pseudoprogressions occur within the first 3 months. Pseudoprogressions represent 52% (12/22) of primary radiological progressions. The use of immune RECIST (iRECIST) criteria should be questioned after 3 months. Majority of patients with pseudoprogression in this study population have favourable outcomes.